Mineralogical Analysis Applied to Forensics A Guidance on Mineralogical Techniques and Their Application to the Forensic Field - Mercurio, Mariano; Langella, Alessio; Di Maggio, Rosa Maria; Cappelletti, Piergiulio (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book illustrates the main modern mineralogical analytical procedures that can be applied for forensic purposes on various typologies of materials and substances and has both theoretical and practical approach. Moreover, it focuses on all those challenges that can arise with forensic analysis, such as the choice of the most proper mineralogical techniques as a function of the material and its quantity, destructive and non-destructive analyses, sampling procedures, mineralogical analysis of micro-traces, correct preparation of the samples, correct calibration and analytical conditions of the laboratory instrumentation. Numerous case studies on criminal offenses against persons, environment and Cultural Heritage are illustrated. .
1. Optical microscopy applied to forensics -- 2. X-ray powder diffraction (XRPD -- 3. Scanning Electron Microscopy, Electron Microanalysis and automated SEM for forensic science -- 4. Infrared spectroscopy -- 5. Raman spectroscopy and forensic mineralogy -- 6. ICP-MS for forensic science -- 7. Simultaneous Thermal Analysis (STA): a powerful tool for forensic purposes -- 8. X-ray fluorescence -- 9. Isotopic analysis techniques applied in forensics. New frontiers of isotope geochemistry -- 10. Image analysis in forensic mineralogy.
Keywords: Mineralogy; Forensic sciences; Soil science; Mineralogy; Forensic Science; Soil Science